Restructuring Routinely Collected Patient Data: ORCA Applied to Andrology - Pierik, F. H.; van Ginneken, A. M.; Timmers’, T.; Stam, H.; Weber, R. F. A. (Methods of Information in Medicine, 1997)
Hospital information systems do not always cover all required detail per specialty. This may lead to scattering of data over disparate systems and the paper record. The ORCA (Open Record for CAre) CPR offers a generic structure for record sharing, and record keeping tailored to specific needs. We studied whether a semantic integration of existing and new data was possible, using the ORCA structure. Existing andrology data, originating from separate sources, were utilized for this purpose. During normalization, validation and explication steps, latent problems in the source data were exposed and removed, followed by a merge with new data items. By conversion of source data to ORCA, a unique representation of medical concepts in the database was attained, facilitating retrieval of univocal data for multiple purposes. We conclude that the expansion to the andrology domain, including transparent integration of existing data, provides support for the generality of ORCA.
Keywords: Data Modeling; Computerized Medical Record Systems; Data Collection; Ambulatory Care Systems